Design of Seamless Knitted Radiation Shielding Garments with 3D Body Scanning Technology. (2015) - Maghrabi, Huda Ahmed; Vijayan, Arun; Wang, Lijing; Deb, Pradip
Abstract: Protective aprons for medical use shield against the effects of radiation. The aprons are universally tailored to fit both male and female bodies without due consideration to the differences that abound between masculine and feminine bodies. To date very little emphasis has been shown on the development of aprons to suit the needs of the female anatomy specifically the breast region as well as consideration of the body shape of pregnant women. This research reviews the needs to develop an X-ray protective garment that is specifically tailored for the female body. Protective aprons designed to fit the female physique incorporating curvature around specific parts of the body namely hip and breast regions as well as the suitability of the apron for use by pregnant women have been explored. Emphasis has been shown on the fit of the garment to impart improved wearer mobility. 3D body scanning technology was used to determine the fit of the developed designs and understand the significance of air gaps between the body and the garment.